Dysphagia Evaluation: The Added Value of Concurrent MBS and Esophagram. (27th January 2021) - Hawkins, Daniel; Cabrera, Claudia I.; Kominsky, Rachel; Nahra, Alexis; Howard, N. Scott; Maronian, Nicole
Abstract : Objectives/Hypothesis: Dysphagia is associated with increased mortality and healthcare costs. The modified barium swallow study (MBS) is the gold standard in assessing oropharyngeal dysphagia, but does not evaluate the esophagus. A barium esophagram can visualize the esophagus but does not evaluate the oropharyngeal swallow, nor does it utilize the expertise of speech and language pathologists. Providers may order one or both studies yet still risk missing critical pathology. Study Design: Retrospective cohort study. Methods: A retrospective chart review was conducted at an academic medical center between January 2016 and June 2019 focused on patients who had both MBS and esophagram as imaging for dysphagia evaluation. Analysis determined whether MBS and esophagram performed concomitantly improved diagnostic clarity. Results: A total of 5, 183 patients underwent 6, 066 swallow studies for dysphagia in the study period. Of which, 124 of these patients had concurrent MBS and esophagram. 10.5% of concurrent studies demonstrated a congruent negative evaluation. 59.7% of patients had an unremarkable MBS or esophagram paired with abnormal findings within the corresponding esophagram or MBS, respectively. 29.8% had both MBS and esophagrams that demonstrated an abnormality, but with unique pathologies identified by each study. In total, 85.1% of unremarkable MBS or esophagrams were paired with abnormal findings in the corresponding esophagram or MBS, respectively. Conclusion: Selection of diagnostic testing is variable among providers and may be influenced by healthcare systems. This analysis revealed that MBS and esophagrams provide unique diagnoses. Concurrent MBS and esophagrams may improve diagnostic accuracy, yet minimize additional studies. National practices around dysphagia diagnostics are inconsistent and would benefit from standardization. Level of Evidence: 4 Laryngoscope, 131:2666–2670, 2021